A framework for selecting lean practices in sustainable product development: The case study of a Brazilian agroindustry. (1st August 2018) - Lermen, Fernando Henrique; Echeveste, Márcia Elisa; Peralta, Carla Beatriz; Sonego, Monique; Marcon, Arthur
Abstract: Literature shows different forms of improving New Product Development performance for sustainable product innovation. To that end, Lean principles are widely disseminated as means for waste elimination, value proposition and continuous improvement in product development. Nevertheless, operationalizing the adoption of such principles requires knowledge regarding the adequate practices for each stage and the typology of the Lean Product Development. The available studies present practices focused on specific Lean practices in product development stages without a systemic vision of the process. This study's objective is to fill this gap by proposing a framework with tools and practices to be implemented throughout the Lean Product Development and by offering a customizable guide to implement the framework. The tools and practices addressing Lean Product Development were divided into phases, resulting in 17 studies and 42 tools/practices. We applied the proposed framework to the case of a fruit processing agroindustry to sustainably develop an innovative solution (Cationic, Anionic, Hydrophobic Modified Starch in Pre-Gel Form) for fruit preservation and to eliminate waste during the product development process. This study presents techniques and methodologies for the development of solutions for the agroindustrial sector. The development of this product was supported by Lean practices and tools, offering reusable knowledge, which preserved fruits for twice the shelf life. The proposed solution presented a 56-day preservation, which presents a 25% higher yield compared to the current best preserving solution (sulfur dioxide). In addition to eliminating the need to purchase a new equipment, since it comprises a similar process to the already existing ones in the fruit processing. Graphical abstract: Image 1 Highlights: Lean principles are used for waste elimination and continuous improvement in NPD. A LPD framework was proposed to offer customizable tools and practices for NPD. Practices and tools are selected according to product typology. The proposed framework was validated in a fruit processing industry. Application of LPD in the push industry is favored.